A216 UC NARRATIVE CANADIAN DATA – COMPARING PATIENT AND PHYSICIAN PERSPECTIVES ON COMMUNICATION AND MANAGEMENT OF ULCERATIVE COLITIS. (15th March 2019) - Panaccione, R; Mawani, M; Kayhan, C; Wosik, K
Abstract: Background: The Ulcerative Colitis (UC) Narrative Study was created to better understand the perspectives of patients (pts) and gastroenterologists (GIs) regarding issues surrounding UC and its management in 10 countries. Aims: Here, we present data from a cross-sectional survey of Canadian pts and GIs. Methods: Surveys were conducted online between Dec 2017 and Feb 2018. Pts (≥18 years) met the following criteria: diagnosis of UC, not had a colectomy, taken prescription (Rx) UC medication beyond 5-aminosalicylates (5-ASAs), and visited a GI/internist in the previous year. Eligible GI physicians were included if they saw ≥10 UC pts per month, if ≥10% of their UC pts were treated with a biologic, and if they did not practice in a long-term care facility. Results: 80 GIs and 215 pts responded (pts' mean age, 42.1 years; 51% male), and current Rx medications included biologics (37%), corticosteroids (34%), 5-ASAs (31%), and immunosuppressants (30%), with 8% of pts receiving no Rx medication. 63% of pts reported their UC being controlled with no/few symptoms, and GIs felt that UC was controlled in 67.8% of their pts on average. In the past year, 89% of all pts reported a flare and experienced a mean of 5.2 flares. The majority of pts (87%) were satisfied with the communication they had with their GI, and 69% had set goals for managing UC. Most pts (80%) were satisfied with their current medication, and GIs believed 77.6% of pts to be satisfied, on average. 67% of pts wished they had more medication choices. Approximately half of pts (52%) wished their GI had discussed all treatment options earlier so they had a better idea of their choice, while 78% of GIs wished they had more time for such discussions. Less than half (42%) of pts had interacted (relied on for information, reached out to, or were referred by their GI) with a pt organization. Only 66% of GIs discussed with their pts the information and support pt organizations can provide, despite 86% of GIs agreeing that pt organizations are important to the management of UC. Pts and GIs agreed on what is most important for UC management – being able to conduct daily activities, avoiding a colectomy and hospitalization. While 98% of GIs wished their pts would talk to them before stopping medications, 38% of pts hesitated to disclose non-adherence to their GI. Conclusions: Canadian pts have positive relationships with their GIs, but opportunities remain regarding understanding pt concerns, setting appropriate goals, and pt education and support, particularly at the time of diagnosis where pt organizations could be an important resource. Funding Agencies: Pfizer Inc